Isolasi dan Seleksi Bacillus sp. dari Ikan Lele (Clarias sp.) serta Potensinya sebagai Probiotik - ., Hamtini; ., Widanarni; Meryandini, Anja (Perhimpunan Biologi Indonesia, 2015)
The aims of this study was to isolate and select Bacillus from the gut of catfish as probiotic candidates in the fish feed production. Isolation was conducted by heating samples at 80 ÃÂ°C for 10-15 minutes using Triptone Soy Agar (TSA) media which have been added with 1% skim milk for proteolytic activity and 1% starch for amylolytic activity. Selection was conducted based on pathogenicity test, antibiotic susceptibility test and total suspended solids. Isolate that have ability to degrade feed would be made the growth curves, analysis of protease and amilase activites and also combination of bacteria isolate with feed. Selected isolates as candidate probiotic were identified furthermore using 6S-rRNA gene. Among 16 isolates, there were 7 isolates that have gamma hemolytic activity (PTB 1.1, PTB 1.2, PTB 1.4, PTB 1.7, STB 1.6, STB 1.1 and STB 2.1). Antibiotic susceptibility test showed that 3 isolates were sensitive to the tested antibiotics (PTB 1.4, PTB 1.7 and STB 1.6). These three selected isolates were tested for their ability to degrade fish feed. PTB 1.4 isolate was able to degrade the feed with the smallest residue on the filter paper (0.0068 g). PTB 1.4 isolate also has proteolytic and amylolytic index of 0.61 and 0.60, respectively. Amylase activity of PTB 1.4 isolate added with 1.2% feed reached the highest peak in 120-hour of observation time (0.399 ÃÂµ/mL) and the highest protease activity was in 72-hour of observation time (6.595ÃÂ ÃÂµ/mL). PTB 1.4 isolate has the ability to degrade the feed with the amount of 106 CFU/mL inoculum. Based on 16S-rRNA gene sequences isolate PTB 1.4 was 99% homolog with Bacillus megaterium. Isolation and selection of probiotic candidate from Clarias sp. get PTB 1.4 was a best isolate that there were not pathogenic, sensitive to antibiotic test, had protease and amilase activities. PTB 1.4 isolate had capability to degrade the feed.ÃÂ Keywords: Bacillus, Clarias sp., probiotic, feedÃÂ